Early specialization and talent development in figure skating: Elite coaches' perspectives - Antonia Cattle; Alexandra Mosher; Alia Mazhar; Joseph Baker (Bern Open Publishing, 2023)
Among the many issues explored by sport science researchers, one topic that seems the least controversial is the recommendation against specialization in early sport training. However, there has been little examination of early specialization in sports where this type of training is the norm. In this study, we explored notions of early specialization and its consequences (i.e psychological, social, and physical) among 7 figure skating coaches (5 males and 2 females) responsible for coaching singles skating (both women and men) at a range of competition levels. Semi-structured interviews with each coach were subjected to a thematic analysis. Themes identified through the analysis revealed coaches were aware and attentive to the potential risks of early specialization and took steps to manage these risks. Moreover, the coaches noted that developing a skater in the environment of elite figure skating required identifying athletes with the right combination of characteristics, and that there were important nuances to developing these athletes in the Canadian context. These findings highlight the complexities of developing a well-rounded athlete in a sport where early specialization is widely accepted as the norm.